Impact of Teachers’ Assessment Practices on Students’ Attitude and Critical Thinking in Basic Science - Musa, Joyce Hassana; Achor, Emmanuel; Agogo, Peter Ogbu (Journal of Multidisciplinary Research and Development, 2025)
This study investigated impact of teachers’ assessment practices on students’ attitude and critical thinking in Basic Science using cross-sectional survey research design. A sample of 393 from a population of 20,885 students using multi-stage sampling procedure participated. Three instruments: Basic Science Critical Thinking Test (BSCTT), Basic Science Students’ Attitude Scale (BSSAS), and Basic Science Teachers’ Assessment Practices Observation Scale (BSTAPOS), with reliability coefficients of .60, .71 and .66 respectively aided data collection. Based on data analysis, it was found that a significant difference exists in the impact of teachers’ low, moderate and high classroom assessment practices on the mean attitude ratings [F(2,392) = 71.483, p = .000 < .05], mean critical thinking scores [F(2,392) = 65.023, p = .000 < .05] of students in Basic Science. Male and female students do not differ significantly on the impact of teachers' low and moderate assessment practices but with high assessment practice on attitude, and also do not differ significantly regarding critical thinking scores in Basic Science. To reduce the incidence of Basic Science teachers’ low and moderate assessment practices, teachers are encouraged to use high classroom assessment practices.